Context Factors Facilitating and Hindering Patient Participation in Dialysis Care: A Focus Group Study With Patients and Staff. Issue 6 (21st July 2020) - Årestedt, Liselott; Martinsson, Caroline; Hjelm, Carina; Uhlin, Fredrik; Eldh, Ann Catrine
Abstract: Background: Safe health care of good quality depends on structured and unceasing efforts to progress, promoting strategies tailored to the context, including elements such as patients' preferences. Although patient participation is a common concept in health care, there is yet limited understanding of the factors that facilitate and hinder it in a healthcare context. Aims: This paper identifies what patients and health professionals depict in terms of enablers and barriers for patient participation in dialysis care. Methods: An explorative qualitative design was applied with seven focus group discussions with patients, staff, and managers across different types of hospitals, with the texts analyzed with content analysis. Results: The dialysis context represents three key elements—people, resources, and interactions—that can both enable and hinder patient participation. Both barriers and facilitators for patient participation were found to reside at individual, team, and organizational levels, with a greater number of enabling factors implied by both patients and staff. Linking Evidence to Action: While the dialysis context comprises opportunities for progress in favor of patient participation, a shared understanding of the concept is needed, along with how contextual factors can facilitate conditions for participation by patient preferences. In addition, the most favorable strategy for implementing person‐centered care is not yet known, but to facilitate patient participation from a patient perspective, creating opportunities to enable staff and patients to share a common understanding is needed, along with tools to facilitate a dialogue on patient participation.